Management of severe aortic valve stenosis in the neonate - Mitchell, B.J.; Brown, S.C. (SA Heart Journal, 2017)
Aortic valve stenosis (AS) causing obstruction to the left ventricular outfl ow, and hence reduction of the cardiac output, remains a therapeutic challenge for paediatric cardiologists and cardiothoracic surgeons. Infants that present at birth may have very dysplastic valves with severe or critical AS and are typically the most diffi cult to treat. This article therefore focuses on the management of severe AS in the neonate. This article also revises the embryology of the semi-lunar valves, as the morphology of the aortic valve often dictates the treatment pathway.